The Japanese Lung Cancer Society Guideline for non-small cell lung cancer, stage IV - Akamatsu, Hiroaki (Int J Clin Oncol, 2019)
According to rapid development of chemotherapy in advanced non-small cell lung cancer (NSCLC), the Japan Lung Cancer Society has been updated its own guideline annually since 2010. In this latest version, all of the procedure was carried out in accordance with grading of recommendations assessment, development and evaluation (GRADE) system. It includes comprehensive literature search, systematic review, and determination of the recommendation by multidisciplinary expert panel which consisted of medical doctors, pharmacists, nurses, statisticians, and patients from patient advocacy group. Recently, we have had various types of chemotherapeutic drugs like kinase inhibitors or immune-checkpoint inhibitors. Thus, the guideline proposes to categorize patients into three entities: (1) driver oncogene-positive, (2) PD-L1 ≥ 50%, and (3) others. Based on this subgroup, 31 clinical questions were described. We believe that this attempt enables clinicians to choose appropriate treatment easier. Here, we report an English version of the Japan Lung Cancer Society Guidelines 2018 for NSCLC, stages IV.